2014
DOI: 10.1186/s12915-014-0087-z
|View full text |Cite
|
Sign up to set email alerts
|

Reagent and laboratory contamination can critically impact sequence-based microbiome analyses

Abstract: BackgroundThe study of microbial communities has been revolutionised in recent years by the widespread adoption of culture independent analytical techniques such as 16S rRNA gene sequencing and metagenomics. One potential confounder of these sequence-based approaches is the presence of contamination in DNA extraction kits and other laboratory reagents.ResultsIn this study we demonstrate that contaminating DNA is ubiquitous in commonly used DNA extraction kits and other laboratory reagents, varies greatly in co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

82
2,829
5
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,692 publications
(3,016 citation statements)
references
References 73 publications
82
2,829
5
6
Order By: Relevance
“…A further limitation is that because we applied stringent quality controls, our sample size was reduced by inability to generate sequencing data from approximately a third of samples, most likely due to low bacterial load. Our qPCR analysis of total bacterial load corroborated previous results showing that the PCR-based profiling of microbiota is reliable with bacterial loads above 10 5 to 10 6 of bacterial genomes per ml Salter et al, 2014). It has been suggested that many microbiota studies generate erroneous results when the sequencing approach developed for bacteria-rich samples, such as gut or vagina, are applied without modification to bacteria-poor sites (Lauder et al, 2016;Salter et al, 2014;Yong, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…A further limitation is that because we applied stringent quality controls, our sample size was reduced by inability to generate sequencing data from approximately a third of samples, most likely due to low bacterial load. Our qPCR analysis of total bacterial load corroborated previous results showing that the PCR-based profiling of microbiota is reliable with bacterial loads above 10 5 to 10 6 of bacterial genomes per ml Salter et al, 2014). It has been suggested that many microbiota studies generate erroneous results when the sequencing approach developed for bacteria-rich samples, such as gut or vagina, are applied without modification to bacteria-poor sites (Lauder et al, 2016;Salter et al, 2014;Yong, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…To limit biases introduced by PCR, we performed a strict sequence quality control. In the future, the use of mock community control, although not common practice at the time of this study, is recommended to quantify sequence contamination (Lusk, 2014; Salter et al., 2014). However, the latter study also show that contamination is more pronounced with samples containing low microbial biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences assigned to chloroplasts, mitochondria, archaea, and eukaryotes were removed based on classification against the Greengenes database (release gg_13_8_99, McDonald et al., 2012). Further, kit contaminants were removed based on sequencing results of PCRs from negative controls, including Brevibacterium casei , B. aureum , Brachybacterium sp., Dietzia sp., Pelomonas puraquae , and Simkania negevensis (Salter et al., 2014). After removal of unwanted sequences, 3,576,201 sequences with an average length of 309 bp were retained for subsequent analyses, clustered into OTUs (97% similarity cutoff), and annotated against the Greengenes database (release gg_13_8_99, bootstrap = 60; McDonald et al., 2012).…”
Section: Methodsmentioning
confidence: 99%